К вопросу о предложно-падежных конструкциях “предлог от + род. п. существительного” со значением опосредованного субъекта в русском языке - Лычинская, М. С. (Kalbotyra, 1994)
The problem, analysed in this article, relates to the communicative syntax. The nominal constructions with preposition “OT” are examined as predicative units in the contracted form.